O terceiro setor na educação de adultos: tensões e ambivalências - Paula Guimarães (Universidade do Minho, 2013)
The third sector has an important role in the promotion of adult education, training and learning as well as in social change in local communities that have been progressively excluded from hegemonic processes of economic development. However, many non-governmental organisations have adopted mediation strategies between the State and local communities in the frame of partnerships and have shared characteristics with enterprises. This fact raises doubts concerning these organisations' autonomy and on their capacity to develop educational and emancipatory projects. This article aims at discussing transformations occurred in the third sector which is involved in adult education. This analysis relates these changes with the erosion of the associations' dynamics. Data discussed was collected within a research project focused on a case study of the public policy of adult education after 1999 and a local development association that promoted specific provision of adult education forms.